(untitled) (Bangladesh Critical Care Journal, 2014)
Background: Urinary tract infections (UTIs) remain the common infections in outpatients as well as hospitalized patients. Current knowledge on antimicrobial sensitivity pattern is essential for appropriate therapy. The aim of the study is to determine the changing pattern of antibiotic sensitivity among uropathogens causing UTI. Methods: Urinary isolates from symptomatic UTI cases attending in Square hospital were processed in the Microbiology lab. Antimicrobial susceptibility testing was performed by Kirby Bauers disc diffusion method. Extended spectrum beta lactamase (ESBL) production was determined by double disk synergy test method. Results: Of the 200 tested sample 110 samples showed growth of pathogens among which the most prevalent were E.coli (58.18%) followed by Enterococci (13.6%). The majority (68.18%) of the isolates were from female. ESBL production was observed in 46.87% o E.coli strains and 25% of Klebsiella strains. More than 98% of the isolates are sensitive to Imipenem, Meropenem , while 86.36% are sensitive to Amikacin, 73.63% to Nitrofurantoin and 74.54% to Gentamicin. Very high rate of resistance is seen against amoxicillin (88.19%), cefixime (65.46%), cotrimoxazole (68.19%) and ceftriaxone (63.63%). E. coli showed high sensitivity to meropenem, imipenem and amikacin (100%) followed by Gentamicin (94.1%). Conclusion: The study revealed that E.coli was the predominant bacterial pathogens of UTIs. An increasing trend in the production ESBLs among UTI pathogens in the community was noted. Nitrofurantoin should be used as empirical therapy for primary, uncomplicated UTIs. DOI: http://dx.doi.org/10.3329/bccj.v2i1.19952 Bangladesh Crit Care J March 2014; 2 (1): 21-24